Liometopum microcephalum (Hymenoptera, Formicidae) у Нижньому Придніпров’ї - Макаревич, О.М. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Liometopum microcephalum Panzer — единственный представитель муравьев, занесенный в Красную книгу Украины. Только 3 популяции этого вида известны на территории Украины, но его биология и экология изучены недостаточно. Нами найдено поселение L. microcephalum на о. Казацкий в приустьевой части Днепра возле Новой Каховки (Херсонская обл.). Исследован ряд особенностей экологии L. microcephalum, которые позволяют сделать вывод о его доминантной роли в многовидовой ассоциации муравьев. Liometopum microcephalum Panzer is the only one ant species included into Red Data Book of Ukraine. Only three populations of this species were known for the territory of Ukraine, but biology and ecology were unstudied. We found population settlement of L. microcephalum on the Kozatsky island of Dnepr river near New Kachovka (Kherson Region). Several biological characters of L. microcephalum are studied, and its dominant role in multispecies ant community are shown.